Overcoming the trade-off relationship between mechanical and adhesive properties of acrylic pressure sensitive adhesive thin-film by reinforcing polydopamine-coated silica nanoparticles. (16th July 2021) - Kim, Seonghyun; Lee, Seung Hui; Choi, Subi; Ahn, Suk-kyun; Jang, Gi-Deog; Park, Jong S.; Seong, Dong Gi
Abstract: PSA-silica nanocomposite thin-films with a thickness of 150 μm were newly fabricated through the optimized process to overcome the typical trade-off relationship where the enhancement of mechanical properties diminishes the strength of adhesive properties. As a consequence of reinforcement with polydopamine-embedded silica nanoparticles, the resulting nanocomposite films showed an 180% increase in tensile strength without a significant loss in peel strength. Viscoelastic behavior of the nanocomposite film was investigated to predict the final physical properties. Lap shear and probe tack tests were successfully performed to verify the reinforcing mechanism overcoming the trade-off relationship. Graphical abstract: Image 1 Highlights: Mechanical and adhesive properties of PSA are mostly trade-off each other. Overcome the trade-off by polydopamine coated Si reinforced nanocomposite PSA. Verify the reinforcing mechanism by investigating physical and viscoelastic behaviors.